Responsabilidade social empresarial: de que forma as empresas vencedoras do projeto desafio de impacto social Google 2016 se beneficiaram e quais foram os impactos indiretos para responsabilidade social no Brasil. - Rocha, Jefferson Rodrigues da (2020)
The objective of the research was to identify the impacts and benefits provided to Brazil by means of the Google 2016 social impact challenge. A descriptive field research was used to identify, record and analyze the characteristics, factors or variables that relate to the phenomenon or process. This type of research can be understood as a case study where, after data collection, an analysis of the relationships between the variables is carried out for a subsequent determination of the resulting effects in a company, that is, the company's opinion regarding company. The research will also be characterized as an explanatory investigation, since the ultimate goal of the research is to identify if technology can influence companies and society.